EUS-guided coil placement for acute gastric variceal bleeding induced by non-EUS-guided variceal glue injection (with video) - Tarek Mazzawi (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound (EUS)-guided coil placement is a new emerging technique for management of gastric varices. In this video case report, we describe an EUS-guided coil placement for managing acute bleeding of gastric varices, following an unsuccessful glue injection to achieve hemostasis.